High‐Performance Polymer Photodetector Using the Non‐Thermal‐and‐Non‐Ultraviolet–Ozone‐Treated SnO2 Interfacial Layer. Issue 3 (10th December 2019) - Deng, Rui; Yan, Chao; Deng, Yadan; Hu, Yufeng; Deng, Zhenbo; Cui, Qiuhong; Lou, Zhidong; Hou, Yanbing; Teng, Feng
Abstract : In organic or perovskite photovoltaic‐type devices, to improve device performance, the thermal and ultraviolet–ozone (UVO) treatments are usually critical for the metal oxide film fabrication by removing the interfacial layer induced defects. However, the defects might play the opposite role in photoconductive photodetectors, where the defect‐induced photogenerated charge accumulation can lead to a tunneling current. Herein, a high‐performance solution‐processed broadband organic photodetector (OPD) in the visible wavelength is realized and characterized by introducing the non‐thermal‐and‐non‐UVO‐treated SnO2 nanoparticle film between the indium tin oxide (ITO) electrode and the active layer of the poly(3‐hexylthiophene) (P3HT):phenyl‐C61‐butyric‐acid‐methyl‐ester (PC61 BM) blend. The untreated SnO2 nanoparticle layer can efficiently block the external charge injection, which considerably reduces the dark current density. Under illumination, the photogenerated charges are accumulated at the interface between the SnO2 layer and the active layer, and thus contribute a tunneling injection, resulting in a significantly high photocurrent. Therefore, the OPD shows a high performance in every figure of merit: external quantum efficiency (EQE) of 1430%, responsivity of 6.97 A W −1, detectivity of 2.29 × 10 13  Jones, and −3 dB bandwidth of 2.8 MHz. The solution‐processed high‐performance photodetectors without thermal and UVO treatments are highly compatible with low cost, flexible, and large‐area electronics. Abstract : An organic photodetector is demonstrated using the non‐thermal‐and‐non‐ultraviolet–ozone (UVO)‐treated SnO2 film, which can efficiently block the external charge injection, and the photocurrent can be considerably increased through tunneling. The best device achieves high‐performance parameters with external quantum efficiency of 1430%, responsivity of 6.97 A W −1, detectivity of 2.29 × 10 13  Jones, and −3 dB bandwidth of 2.8 MHz.